Testing the Process Dissociation Procedure by Behavioral and Neuroimaging Data: The Establishment of the Mutually Exclusive Theory and the Improved PDP - Zhang, Jianxin; Wang, Xiangpeng; Huang, Jianping; Chen, Antao; Liu, Dianzhi (Frontiers in Psychology, 2020)
The process dissociation procedure (PDP) of implicit sequence learning states that the correct inclusion-task response contains the incorrect exclusion-task response. However, there was no research to test the hypothesis. The current study used a single variable (Stimulus Onset Asynchrony (SOA): 850 ms vs. 1350 ms) between-subjects design, with pre-task resting-state fMRI, to test and improve the PDP to the mutually exclusive theory (MET). (1) Behavioral and neuroimaging data demonstrated that classical PDP was not validated. In the SOA = 850 ms group, the correct inclusion-task response was at chance, but the incorrect exclusion-task response occurred greater than chance, and the two responses were not correlated. But in the SOA = 1350 ms group, the two responses were in contrast to each other. In each group, brain areas whose amplitude of low frequency fluctuations (ALFFs) in the resting-state related to the two responses were either completely different or opposite to one another. However, the results were perfectly consistent with the MET proposed by the present study which suggests that the correct inclusion-task response is equal to the correct exclusion-task response is equal to C + A1, and the incorrect exclusion-task response is equal to A2. C denotes the controlled response and A1 and A2 denote two different automatic responses. (2) The improved PDP was proposed to categorize the 12 kinds of triplets as delineating four knowledge types, namely non-acquisition of knowledge, uncontrollable knowledge, half-controllable knowledge, and controllable knowledge with the MET. ALFFs in the resting-state could predict the four knowledge types of the improved PDP. The participants’ control of the four knowledge types (degree of consciousness) gradually improved. Correspondingly, the brain areas in the resting-state positively related to the four knowledge types, gradually changed from the sensory and motor network to the somatic sensorimotor network, and to the implicit learning network, and then to the consciousness network. The brain areas in the resting-state negatively related to the four knowledge types gradually changed from the consciousness network to the sensory and motor network. As SOA increased, the brain areas associated with almost all the four knowledge types changed.